2018
DOI: 10.1136/bmjopen-2017-019640
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of personalised remote long-term follow-up of people with cochlear implants: a randomised controlled trial

Abstract: Introduction Substantial resources are required to provide lifelong postoperative care to people with cochlear implants. Most patients visit the clinic annually. We introduced a person-centred remote follow-up pathway, giving patients telemedicine tools to use at home so they would only visit the centre when intervention was required. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…com/EANDH/B66, which displays health statue utility values reported in included studies). One study reported substantially lower mean HSUV for bilateral cochlear implant compared with other studies (0.41 and 0.04), although sample sizes for these estimates were low at n = 2 and n = 3 (Cullington et al 2018). Two studies reported vignette-based HSUV estimates whereby HSUV were obtained from responses from participants other than patients with the condition.…”
Section: Bilateral Cochlear Implantsmentioning
confidence: 95%
See 2 more Smart Citations
“…com/EANDH/B66, which displays health statue utility values reported in included studies). One study reported substantially lower mean HSUV for bilateral cochlear implant compared with other studies (0.41 and 0.04), although sample sizes for these estimates were low at n = 2 and n = 3 (Cullington et al 2018). Two studies reported vignette-based HSUV estimates whereby HSUV were obtained from responses from participants other than patients with the condition.…”
Section: Bilateral Cochlear Implantsmentioning
confidence: 95%
“…Zwolan et al (2014) compared those aged 65 years and older to those under age 65 years and did not detect a significant difference in HUI-3 derived HSUV pre-or postunilateral cochlear implantation, but did observe a greater mean improvement in HUI-3 hearing single attribute utility for the older cohort. In a randomized trial, Cullington et al (2018) found that standard in-person versus remote audiology care had no detectable effect on unilateral or bilateral cochlear implant HSUV.…”
Section: Unilateral Cochlear Implantmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochlear implants share similarities with DBS, requiring timely power source management. Cochlear implant clinicians and patients extensively utilize telehealth checkups, resulting in empowerment and improved hearing outcomes [26][27][28] similar to DBS.…”
Section: Strategies For Ipg Management In Other Devicesmentioning
confidence: 99%
“…Another population-based study from Ontario identified geographical location as a factor for delayed pediatric cochlear implantation (amongst other factors including progressive HL, complex medical conditions, and family indecision)with tele-audiology, these pediatric patients could potentially receive improved access to the hearing care despite their geographic status, which may help alleviate burdens on both themselves and the medical system down the line [Nassiri et al, 2022]. A recent randomized controlled trial also demonstrated the feasibility of personalized remote long-term follow-up care for patients with CI [Cullington et al, 2018]. Follow-up care after IHD (particularly for CI) can be lengthy during the first year and often becomes a time-consuming task for patients when distance traveled is factored in.…”
Section: Ihd In Ontariomentioning
confidence: 99%